The Management Human Resources Sport Based Improvement of Development Index Sport in Padang City West Sumatera - Zalaff, Katsran; Hidayatullah, M.Furqon; Kristiyanto, Agus (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
Sport Development Index is a way to measure the improvement of sport development in a region. This research measures sport development by using sports human resource management in Padang as the indicator. The purpose is to discover the quality of sports human resource management in Padang examined from Sport Development Index and to analyze the availability of sports human resource. This research is conducted in Padang, West Sumatra Province, by taking data from 3 institutions as the scope of studies including the Education Authority, National Sports Committee of Indonesia (KONI), and a local non-formal institution. The research method applies qualitative and quantitative approaches. The qualitative data is collected through observation, document analysis and interview, while the quantitative data is taken by using a norm method of Sport Development Index. The result shows that the number of sport development in Padang based on the index of sports human resource management is 0.00082. According to the Sport Development Index, this number is within the range of 0.000-0.499. It means that sports human resource management belongs to low category quantitatively and qualitatively, or in the other words the quantity is deficient and the quality is low. To conclude, the sport development in Padang belongs to low category, thus the regional government needs to pay more attention and improve the sport development in the city.